ON ZERO-SPACES OF NIKOLSKII-BESOV TYPE - Baghdasarian, A. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
In the paper are considered the generalized spaces of Nikolskii-Besov type with zero upper indexes born from some functions with polynomial growth. In contrast to the corresponding H-spaces of Sobolev-Liouville type, which in case of upper index do not depend the function born from, the considered spaces in general don’t have this property. The paper gives the proof of this fact and some embedding theorems are proved.